2020
DOI: 10.1111/1365-2656.13352
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection patterns are density dependent under the ideal free distribution

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 108 publications
(233 reference statements)
6
76
0
Order By: Relevance
“…Such context dependencies are in fact so common that we do not know of a single instance where researchers were looking for them and failed to find them. Recently, Avgar et al (2020) showed that such context dependencies in habitat-selection patterns are expected to emerge even under the simplest theoretical model of an Ideal Free Distribution (Fretwell, 1969).…”
Section: Sensitivity Of Selection Coefficients To Species Population Density and Habitat Availabilitymentioning
confidence: 99%
“…Such context dependencies are in fact so common that we do not know of a single instance where researchers were looking for them and failed to find them. Recently, Avgar et al (2020) showed that such context dependencies in habitat-selection patterns are expected to emerge even under the simplest theoretical model of an Ideal Free Distribution (Fretwell, 1969).…”
Section: Sensitivity Of Selection Coefficients To Species Population Density and Habitat Availabilitymentioning
confidence: 99%
“…Such context dependencies are in fact so common that we do not know of a single instance where researchers were looking for them and failed to find them. Recently, Avgar et al [85] showed that such context dependencies in habitat-selection patterns are expected to emerge even under the simplest theoretical model of an Ideal Free Distribution [86]. Thus, habitat-selection models often have poor predictive capacity when transferred across different study areas, or even within the same area over time [45].…”
Section: Sensitivity Of Selection Coefficients To Species Population mentioning
confidence: 99%
“…The estimated roe deer population density was low, ranging between 1-3 animals/km 2 (48). Hence, density was not expected to affect habitat selection behaviour (25,27). Between 2005 and 2012, 168 roe deer individuals were monitored (see Details on roe deer capture and data processing in Appendix S1a).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Functional response is usually presented as the effect of availability on odds ratios (13,15) or on the selection coefficients (10,23,25). Although the relationships revealed by RSFs may indicate the presence of a functional response, they are difficult to interpret and to quantify (4,26,27) as they represent selection for or against a certain habitat but do not directly depict the relation between the availability and the actual use of a habitat (e.g. 15,28).…”
Section: Introductionmentioning
confidence: 99%